Understanding ESL Teachers’ Agency in Their Early Years of Professional Development: A Three-Layered Triadic Reciprocity Framework - Huang, Jing; Yip, Jesse W. C. (Frontiers in Psychology, 2021)
This study examined how three Hong Kong secondary ESL (English as a second language) teachers exercised their teacher agency to take control of their teaching and professional development through the lens of the Triadic Reciprocity Framework. More specifically, the study aimed at exploring how teachers’ intentions and actions for the establishment of their professional identity were afforded and constrained by their workplaces. Findings reveal that these ESL teachers exercised different degrees of proactive, reactive, and passive agency. The four properties of human agency, i.e., intentionality, forethought, self-reactiveness, and self-reflectiveness, influenced the teachers’ proactive, reactive, and passive agency when they responded to personal, behavioral, and environmental determinants. The findings shed light on a three-layered Triadic Reciprocity framework on teacher agency and contributes to a more systematic discussion of the various internal and external factors that might exert influences on early career teachers’ sense of agency. This study offers pedagogical implications for school teachers, school leaders, and policy makers in Hong Kong and beyond.